Case Report: AL Amyloidosis Severe Restrictive Cardiomyopathy Associated With Multiple Myeloma—Diagnostic Difficulties - Kirichenko, Yulia Y.; Ilgisonis, Irina S.; Nakhodnova, Elena S.; Sokolova, Irina Y.; Bochkarnikova, Olga V.; Kardanova, Sabina A.; Lyapidevskaya, Olga V.; Privalova, Elena V.; Ershov, Vladimir I.; Belenkov, Yurii N. (Frontiers in Cardiovascular Medicine, 2022)
Background Cardiac AL amyloidosis as a complication of multiple myeloma (MM) is a formidable life-threatening condition. The first-line therapy for both MM and systemic AL amyloidosis is proteasome inhibitors (PIs). Unfortunately, the use of PIs may lead to cardiovascular toxicity development, which requires specific cardio-oncology supervision. Case Report A 57-year-old woman was admitted to a university hospital with clinical manifestation of progressive chronic heart failure. The patient had hypertension and no history of diabetes mellitus, myocardial infarction (MI), stroke, and arrhythmias. After a series of laboratory and instrumental examination methods, MM complicated by cardiac AL amyloidosis was proved. Upon specific cardio-oncology examination (NT-proBNP 4,274 pg/ml), ECHO showed systolic dysfunction, motion abnormalities in LV basal and middle segments, and a typical depositional myocardium pattern (“luminescence”); cardiac MRI revealed restrictive cardiomyopathy and specific hyperenhancement of the ventricles and atria; 24-h ECG showed QS-pattern in leads V1–V3 and unstable ventricular tachycardia (VT) paroxysms. Cardio-oncology consultation showed baseline cardiovascular risk was very high (≥20%), and cardioprotective therapy [iACE/ARBs, beta-blockers (BB), statins] was administered. The patient underwent VCD (bortezomib; cyclophosphamide; dexamethasone) chemotherapy (CMT) program. By the time of publication, the patient had received four CMT courses with a positive oncohematological and cardiovascular effect. Conclusion In this clinical case, we described a complication of MM, which was rare according to the severity and manifestation with restrictive cardiomyopathy due to secondary cardiac amyloidosis. The case's features were difficulties in verifying the underlying disease and its own complication, and the complexity of patient management according to modern principles of cardio-oncology.